P491 Determining recommended chlamydia and gonorrhea treatment using linked medical claims, prescription and laboratory data. (14th July 2019) - Tao, Guoyu; Workowski, Kimberly; Bowden, Katherine; Pearson, William; Sullivan, Jane; Henk, Henry; Gift, Thomas
Abstract : Background: The Centers for Disease Control and Prevention (CDC) recommends specific regimens for treatment of chlamydia and gonorrhea. Dual therapy is recommended for gonococcal infection to mitigate antimicrobial resistant gonorrhea (250 mg ceftriaxone plus 1g azithromycin). Previous studies examining adherence to these recommendations have had limited information on medical claims, prescription claims, and laboratory data in private practices in the United States. Methods: We used the OptumLabs® Data Warehouse (OLDW) a comprehensive, longitudinal, real-world data asset with de-identified lives with linked private insurance claims and clinical information to identify persons aged 15–60 years who had valid nucleic acid amplified testing results demonstrating gonorrhea or chlamydia in 2016–2017. We defined valid lab results as positive or negative, but did not include lab records with indeterminate or missing results in our analysis. We then assessed the time of their first positive test and the type of treatment within 30 days to determine if there was evidence in the claims record that the CDC recommended treatment was provided. Results: 4, 972 patients were identified as having gonorrhea only. Of this group, 77% were male, and 70% were 15–35 years of age. Additionally among this group, 35% had evidence of receiving the CDC recommended combination therapy for gonorrhea, 26% had evidence of receiving 250 mg ceftriaxone without evidence of receiving 1g azithromycin, and 16% had evidence of receiving 1g azithromycin without ceftriaxone. A separate group of 24, 044 patients were identified as having chlamydia only. Among this group, 40% were male, and 88% were 15–35 years of age. Additionally among this group, 65% had evidence of receiving a CDC-recommended chlamydia treatment, and 11% also had evidence of receiving 250 mg ceftriaxone. Conclusion: There is variation in claims data regarding the treatment regimens administered for gonorrhea and chlamydia treatment. Further studies are needed to evaluate treatment claims data against medical record reviews. Disclosure: No significant relationships.